Can the Concept of Integrated Reporting Be an Inspiration for the New Accounting Pragmatism? - Kwiecień, Mirosława (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The publication presents dilemmas related to accounting in the modern global economy. In economic discourses, it is explicitly indicated that accounting as a transcription technique is only an instrument, like all techniques, for achieving different goals. The question arises, are we the accountants approving these statements, this diagnosis? Did it affect the status of accounting as a science in the Polish academic environment? Why finance, especially financial economics, which in quantitative terms, such as the theoretical innovations of H. Markowitz (and other Nobel Prize winners, eg E. Famy) that made it possible to convince investment fund managements that their portfolios are still just as safe, despite the fact that have they become more and more risky, have they not suffered as a scientific discipline? These are difficult questions that were (and are) formulated by many representatives not only of our scientific discipline – among others also many Nobel Prize winners, eg J. Stiglitz, R. Schiller pointing out the “weaknesses” of the theory of finance, especially economy. One can ask the question – on the basis of searching the scientific literature (perhaps its debatable choice) – about the value of prediction of accounting theory implying predictions of economic facts, as well as the question about new accounting pragmatism, about corporate social responsibility, about risk management in the context of rationality in the sense of Aristotle, J. Kant, M. Heller, T. Kotarbiński. The aim of the publication is to indicate for what reasons the discourse on the change in accounting pragmatism should begin, so that this opportunity, apart from purely logical, becomes a real possibility. In the preparation of the publication, the analytical method of research was used, which was supported by the induction and deduction method.